EFEKTIVITAS (LIQUID SMOKE) ASAP CAIR TEMPURUNG KELAPA (COCOS NUCIFERA) TERHADAP PERTUMBUHAN ESCHERICHIA COLI - Diah Sudiarti (Pendidikan Biologi,Universitas Islam Jember, 2015)
The Liquid smoke is the dipersion of the Smoke in the air as the result of distillation or biomass pyrolysis of Cocos nucifera. This research was to know the effectiveness of Liquid smoke of Cocos nucifera to the growth of E. coli. The research was done in Microbiology Laboratory of the Medical Faculty of Jember University. This research is laboratorist experimental with used CRD (Completely Randomized design) with 3 times repetition. The data analysis used SPSS version 11 with Anova and Duncan. This research use some concentration, there are is 12,5%, 25%, 50%, and 100%, positiv control (klorin), and negatif control (aquades). The result of experiment by using Anova, it was kwon that Liquid smoke of in the concentration 12,5%, 25%, 50%, and 100%, to E. Colihave significance value is 0,00 (P<0,05), so every treatment has different result significantly. Whereas, the Duncan analysis showed 100% significantly different with another concentration, including positive and negative control. The 50% concentration has significant different with the 12,5% concentration, and the 25% concentration also has different result with K+ and K-. Whereas K+, K-, and 12,5% has didn’t different.That result proved that Liquid smoke can resist the growth of E. Coli.Key Word :Escherichia coli, Liquid Smoke.